Birthdate study of GABAergic neurons in the lumbar spinal cord of the glutamic acid decarboxylase 67-green fluorescent protein knock-in mouse - Jing eHuang; Jing eChen; Wen eWang; Guo-Hong eCai; Yan-Yan eWei; Shengxi eWu (Frontiers Media S.A., 2013)
Despite the abundance of studies on γ-aminobutyric acid (GABA) ergic neuron distribution in the mouse developing spinal cord, no investigation has been devoted so far to their birthdates. In order to determine the spinal neurogenesis of a specific phenotype, the GABAergic neurons in the spinal cord, we injected bromodeoxyuridine (BrdU) at different developmental stages of the glutamic acid decarboxylase (GAD)67-green fluorescent protein (GFP) knock-in mice. We thus used GFP to mark GABAergic neurons and labeled newly born cells with the S-phase marker BrdU at different embryonic stages. Distribution of GABAergic neurons labeled with BrdU was then studied in spinal cord sections of 60-day old mice. Our birthdating studies revealed that GABAergic neurogenesis was present at embryonic day 10.5 (E10.5). Since then, the generation of GABAergic neurons significantly increased, and reached a peak at E11.5. Two waves for the co-localization of GABA and BrdU in the spinal cord were seen at E11.5 and E13.5 in the present study. The vast majority of GABAergic neurons were generated before E14.5. Thereafter, GABA-positive neuron generation decreased drastically. The present results showed that the birthdates of GABAergic neurons in each lamina were different. The peaks of GABAergic neurogenesis in lamina Ⅱ were at E11.5 and E13.5, while in lamina I and III, they were at E13.5 and E12.5 respectively. The present results suggest that the birthdates of GABAergic neurons vary in different lamina and follow a specific temporal sequence. This will provide valuable information for future functional studies.